Competition, not socialism, necessary to society - Midgley, Alfred K. (My University, 1891)
Introduction: The cry for reform has always been the characteristic refrain of the lower classes of society. All people seem to have sufficient self-approbation to think that if things were as they should be their position would in consequence fall in with the highest class of their community; and it can hardly be devised that this is a more prominent fracture of the beliefs of the ignorant than of the educated. This is probably the main reason why we find that the greater part of the socialists belong to the lower element of society. Though of course it would naturally be the discontented ones that would want a revolution. Those being willing to risk the loss of their present benefits for the chance of having their condition bettered. It must be admitted that the present position of the common laborer in the world is not an enviable one. Yet it is impossible for all to be rich, and practically impossible for all to be talented; and it is well for man that it should be so in order that he may satisfy his needs in his present state of development.
Citation: Midgley, Alfred K. Competition, not socialism, necessary to society. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Competition; Socialism; Classism; Class system; Society; Sociology; Theses; Manuscripts (documents)